Multilocational testing of chickpea for field resistance to Ascochyta blight - B.L. JALALI2, M.P. HAWARE1, J. NARAYANA RAO1, HARICHAND2, A.M. GHANEKAR1 and (Indian Phytopathology, 2002)
Chickpea breeding and germplasm lines identified as resistant or moderately resistant to Ascochyta blight (A. rabiei) in field screening at Hisar, Haryana, India, were evaluated for Ascochyta blight resistance at 8 locations in the Indian subcontinent (7 in India, and 1 in Pakistan) between 1990 and 1993. In each location some lines were resistant or moderately resistant. Five breeding lines, ICCX-800859-BPN-BPN-BPN-(-)-3BPN-HWR-BH, ICCX-810800-3H-BW-BH-1H-1H-BH, ICCX-810737-BPN-BPN-BPN-3PN-BH, ICCX-810974-BH-BW-56H-1H-1H-1HWR-BH and ICCL 86447, were resistant or moderately resistant at 5 or 6 of the 8 locations. These lines were moderately resistant or susceptible to Ascochyta blight when tested in a plant growth room at ICRISAT.